PENGARUH AKTIFITAS PACARAN TERHADAP MOTIVASI BELAJAR PADA SISWA KELAS XI SMK PEMUDA PAPAR - Afriansyah, Alik Bima; Khususiyah, Khususiyah; Krisphianti, Yuanita Dwi (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2018)
This study is based on the observation and experience of the researcher, that courtship is used to motivate themselves, students who have positive perception of courtship will be motivated to compete with each other to be able to achieve optimal learning achievement. Conversely with students who have less courageous activity will have limitations in achieving learning achievement. This research uses a quantitative approach with associative causal techniques. The process of data analysis using the help of SPSS 23.00 for windows program using product moment correlation test. The sample of this research are 30 students taken by using simple random sampling. Data collection using questionnaire activity dating activity and questionnaire motivation to learn. The result of data analysis using product moment correlation test showed the influence of dating activity on learning motivation to get value r_hitung 0,415> r_tabel 0,361 with 5% significance level. So it can be concluded that Ha sounded no influence of courtship activity on learning motivation in grade XI students at SMAN PEMUDA PAPAR academic year 2016/2017. Based on the results of research conducted researcher suggestions that need dikemukanan is as one of the materials to improve student learning motivation with the help of a boyfriend or friend.